Micro/mesoporous LTL derived materials for catalytic transfer hydrogenation and acid reactions of bio-based levulinic acid and furanics - Antunes, Margarida M.; Silva, Andreia F.; Fernandes, Auguste; Ribeiro, Filipa; Neves, Patrícia; Pillinger, Martyn; Valente, Anabela A. (Frontiers in Chemistry, 2022)
The biomass-derived platform chemicals furfural and 5-(hydroxymethyl)furfural (HMF) may be converted to α-angelica lactone (AnL) and levulinic acid (LA). Presently, LA (synthesized from carbohydrates) has several multinational market players. Attractive biobased oxygenated fuel additives, solvents, etc., may be produced from AnL and LA via acid and reduction chemistry, namely alkyl levulinates and γ-valerolactone (GVL). In this work, hierarchical hafnium-containing multifunctional Linde type L (LTL) related zeotypes were prepared via top-down strategies, for the chemical valorization of LA, AnL and HMF via integrated catalytic transfer hydrogenation (CTH) and acid reactions in alcohol medium. This is the first report of CTH applications (in general) of LTL related materials. The influence of the post-synthesis treatments/conditions (desilication, dealumination, solid-state impregnation of Hf or Zr) on the material properties and catalytic performances was studied. AnL and LA were converted to 2-butyl levulinate (2BL) and GVL in high total yields of up to ca. 100%, at 200°C, and GVL/2BL molar ratios up to 10. HMF conversion gave mainly the furanic ethers 5-(sec-butoxymethyl)furfural and 2,5-bis(sec-butoxymethyl)furan (up to 63% total yield, in 2-butanol at 200°C/24 h). Mechanistic, reaction kinetics and material characterization studies indicated that the catalytic results depend on a complex interplay of different factors (material properties, type of substrate). The recovered-reused solids performed steadily.